Kompetensi Profesional Guru Rumpun Mata Pelajaran PAI di Madrasah Ibtidaiyah (MIN) II Model Samarinda - Riswadi, Riswadi (SYAMIL: Journal of Islamic Education, 2020)
This research aims to find out how professional teachers of Islamic religious education subjects in the MIN 2 Model Samarinda. This research uses an emics perspective, which is trying to understand, internalize, and describe the professional image of the teacher according to the phenomena and data, so it is also called the phenomenological fact. Data Collection techniques using observations, interviews and documentation, while the data analysis techniques to be used in this study, "descriptive analytic" and in qualitative research generally began since data collection, data reduction, data presentation, and withdrawal of conclusions or verification. The results of the study is that the teacher  is quite professional on the grounds that from the 11 indicators that are determined most have been able to be mastered/implemented well that is able to master the teaching materials, able to understand and interpret the results of educational research for the purposes of teaching, able to manage teaching programs, able to use the media and learning resources, able to plan teaching programs, able to manage the interaction of learning teaching, mastering various methods of teaching, able to recognize and organize the administration of the school (curriculum or learning administration), able to assess the achievement of students for the sake of teaching as well as the ability to master the education foundations, ability to know the functions and services of guidance and counseling that can not recognize children who have special characteristics and ability to manage classes Thus, the learning evaluation of teachers has the ability to assess students ' achievements for the sake of teaching. In this case the teachers of the most specific special PAI class in MIN 2 Model Samarinda have been able to assess well the proven list of values, group books, and analysis of the results are organized neatly and document the governance.